The mystery of the Marajoara : An ecological solution - Meggers, B. J. (Amazoniana, 2001)
For more than a century, the beautiful pottery from artificial mounds on the island of Marajó at the mouth of the Amazon has found its way into museums and private collections in Europe and North America, as well as Brazil.
Keywords: Ilha de Marajó